Comparative Analysis of Elderly Patients Undergoing Radical Cystectomy With Ureterocutaneostomy or Ileal Conduit With a Special Focus on Bowl Complications Requiring Surgical Revision - Mally, David; John, Patricia; Pfister, David; Heidenreich, Axel; Albers, Peter; Niegisch, Günter (Frontiers in Surgery, 2022)
Objectives Ileal conduits (ICs) carry an additional perioperative complication risk due to the bowel procedure. This analysis compares surgical outcomes in patients ≥75 years of age with ureterocutaneostomy (UCN) and IC after cystectomy (Cx). Methods Data of 527 patients included in a retrospective cystectomy database of two high volume centers (2008–2020) were queried to identify elderly patients (≥75 years) who underwent Cx either with IC or UCN. Patient characteristics of all patients [age, BMI, Charlson Comorbidity Index (CCI)], perioperative parameters (operation time, blood loss, transfusions, tumor stage), and postoperative complications (clavien >IIIA, intensive care unit (ICU) stay) were compared. As special focus, bowel complications requiring surgical revision (rBCs) were analyzed. In patients with IC, the rate of ureteral implantation stenosis (USt) was recorded. As a population of special interest, patients ≥80 years of age were analyzed separately. Categorical data were compared using Fisher exact test, and continuous data were compared using Mann–Whitney U test. Results A total of 163 patients ≥75 years of age (125 IC, 38 UCN) were identified. Patients with UCN were older and presented with a higher CCI, though differences were not statistically different. Surgery with palliative intent was more frequent in patients with UCN (37 vs. 10%). Operation time in UCN was significantly shorter (233 vs. 305 min, p = 0.02), while blood loss and transfusion rate were comparable. Overall complication rate (Clavien-Dindo grade IIIA–IVB) was comparable (UCN 34% vs. IC 37%). However, rBC was a rare complication in UCN (3/38) as compared to patients with IC (15/125). Frequency of postoperative ICU stay (UCN 16% vs. IC 16%) and 90-day mortality did not differ (UCN 3/38 patients, IC 5/125 patients). Regarding long-term follow-up, USt requiring revision or permanent stenting was seen in 18/125 (14%) patients with IC. In patients >80 years of age, results were comparable to the main cohort. Low event rate regarding complications and bias inherent of a retrospective analysis (selection bias, unequal distribution in case numbers) precludes detection of statistical differences regarding patients' characteristics and overall complication rate. Conclusion UCN is an alternative to IC in elderly and/or frail patients. Severe bowel complications are numerically less frequent and operation time is minimized.